2017
DOI: 10.1111/1744-7917.12515
|View full text |Cite
|
Sign up to set email alerts
|

Resin foraging dynamics in Varroa destructor‐infested hives: a case of medication of kin?

Abstract: Social insects have evolved colony behavioral, physiological, and organizational adaptations (social immunity) to reduce the risks of parasitization and/or disease transmission. The collection of resin from various plants and its use in the hive as propolis is a clear example of behavioral defense. For Apis mellifera, an increased propolis content in the hive may correspond to variations in the microbial load of the colony and to a downregulation of an individual bee's immune response. However, many aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 70 publications
0
14
1
Order By: Relevance
“…The lack of significant differences observed between infected and uninfected honey bees in our choice, scan and food consumption tests did not support the hypothesis that bees therapeutically use propolis in self-medication. In contrast to our findings, Simone-Finstrom and Spivak [46] and Pusceddu et al [47] suggest propolis may be used by honey bees in self-mediation. However, these two latter studies addressed the role of propolis not against N. ceranae but against two other hive enemies (A. apis and V. destructor) and were conducted in an apiary rather than in the laboratory.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The lack of significant differences observed between infected and uninfected honey bees in our choice, scan and food consumption tests did not support the hypothesis that bees therapeutically use propolis in self-medication. In contrast to our findings, Simone-Finstrom and Spivak [46] and Pusceddu et al [47] suggest propolis may be used by honey bees in self-mediation. However, these two latter studies addressed the role of propolis not against N. ceranae but against two other hive enemies (A. apis and V. destructor) and were conducted in an apiary rather than in the laboratory.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, our study dealt with self-medication by bees for the benefit of the individual bee, and it is very likely that the mechanisms that regulate the response of an infected individual are different from those that regulate the response of uninfected individuals (resin foragers) to the infection of their nestmates. Propolis may therefore be used in colony-level self-medication against some pathogens and pests [46,47] but not in individual-level self-medication against Nosema. We note, though, that Gherman et al [49] did observe individual self-medication by N. ceranae-infected honey bees, though different honeys as opposed to propolis were preferred by bees in those experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, Sustainability 2020, 12, 2302 3 of 16 the appearance of acaricide resistance and the risk of contamination of the bee product have led to increased interest in alternative control strategies against Varroa [20][21][22]. In recent years, great attention has focused on the use of environmentally safe chemicals (such as organic acids), essential oils, and biotechnical methods, and integrated management is recommended [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ethanolic extracts of German propolis were highly toxic to Varroa destructor, with a 10% w/v solution being lethal at 5 s contact [90], and Pusceddu et al observed that raw propolis highly significantly increased the lifespan of Varroa-infected bees, almost completely reversing Varroa-associated mortality [91]. Moreover, the addition of natural propolis to hives reduced the titer of Varroa-transmitted deformed wing virus (DWV) [92] and Varroa-infected colonies specifically increased resin foraging [93]. It is not yet clear which chemical agents in propolis reduce the impact of Varroa infestation, but it was reported that the total polyphenolic content of propolis correlated with levels of Varroa infection in experimental hives in Sardinia [91].…”
Section: Evidence For Propolis Protection Against Bee Infectionsmentioning
confidence: 99%